Association of Body Mass Index with Mortality in Peritoneal Dialysis Patients: A Systematic Review and Meta-Analysis. Issue 3 (May 2016) - Ahmadi, Seyed-Foad; Zahmatkesh, Golara; Streja, Elani; Mehrotra, Rajnish; Rhee, Connie M.; Kovesdy, Csaba P.; Gillen, Daniel L.; Ahmadi, Emad; Fonarow, Gregg C.; Kalantar-Zadeh, Kamyar
Background: Although higher body mass index (BMI) is associated with better outcomes in hemodialysis patients, the relationship in peritoneal dialysis (PD) patients is less clear. We aimed to synthesize the results from all large and high-quality studies to examine whether underweight, overweight, or obesity is associated with any significantly different risk of death in peritoneal dialysis patients. Methods: We searched MEDLINE, EMBASE, Web of Science, CINAHL, and Cochrane CENTRAL, and screened 7, 123 retrieved studies for inclusion. Two investigators independently selected the studies using predefined criteria and assessed each study's quality using the Newcastle-Ottawa Quality Assessment Scale. We meta-analyzed the results of the largest studies with no overlap in their data sources. Results: We included 9 studies ( n = 156, 562) in the systematic review and 4 studies in the meta-analyses. When examined without stratifying studies by follow-up duration, the results of the studies were inconsistent. Hence, we pooled the study results stratified based upon their follow-up durations, as suggested by a large study, and observed that being underweight was associated with higher 1-year mortality but had no significant association with 2- and 3- to 5-year mortalities. In contrast, being overweight or obese was associated with lower 1-year mortality but it had no significant association with 2-, and 3- to 5-year mortalities. Conclusion: Over the short-term, being underweight was associated with higher mortality and being overweight or obese was associated with lower mortality. The associations of body mass with mortality were not significant over the long-term.